Amelioration of postpartum fertility with energy, chelated minerals and vitamins supplements in Dangi cows - Shelar, Raju R; Pandey, Vimal A; Gulvane, Sarita U; Chaudhari, Ravindra J; Gaikwad, Sandeep M; Ambhore, Gajanan S (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The study involved 24 post-partum Dangi cows with a body score of 3 ± 0.5, and 2-5 parity, which were randomly divided into four groups. Group I (n=6) was the untreated control group, group II (n=6) was fed an additional 30 gm daily chelated minerals and vitamins supplement, group III (n=6) was fed an additional 100 gm daily energy supplement, and group IV (n=6) was fed an additional 100 gm daily energy supplement and 30 gm daily chelated minerals with vitamins apart from routine feeding schedule for 50 days post-partum period. The cows in group IV showed 100 % post-partum ovarian activity earlier than in other groups. The first post-partum estrus (PPE) was observed in cows 6/6, 5/6, 4/6, and 3/6 in groups IV, III, II, and I, respectively. Although the difference was statistically non-significant, the average period required for the exhibition of the first PPE was lowest (68.50 ± 0.60 days) in group IV followed by group II (71.25 ± 0.49days), group III (72.00 ±0.49days) and 88.67 ± 0.55days in group I. The researchers found that the first service conception rate (FSCR) was highest in group IV (66.66%) followed by group II (50%), group III (40%), and group I (33.33%). The number of days open were 91.00 ± 00, 75.5 ± 0.31, 85.00 ± 0.63, and 70.00 ± 0.60 in groups I, II, III, and IV, respectively, and did not differ significantly. Although the results were non-significant, it suggests that implementing chelated minerals, vitamins, and energy supplements could be a promising strategy to expedite uterine involution, resume ovarian cycles, enhance estrus behavior, increase first service conception rate, decrease days open, and improve reproductive efficiency in post-partum cows. Supplementation of energy, chelated minerals, and vitamins did not significantly impact serum biochemical parameters like glucose, urea, albumin, globulin Ca, P, and Mg levels.